The Relationship between Anxiety Level and Comfort Level with Sleep Quality in Preoperative Patients at Cilacap Regional Hospital - Maulana, Gading Esa; Sebayang, Septian Mixrova; Yanti, Linda (Menara Journal of Health Science, 2024)
Surgery is a medical procedure that uses invasive techniques to open or expose a part of the body, generally by making an incision in the area to be treated, making repairs, and closing the wound with sutures. Certain operations can cause varying degrees of anxiety in individuals. For minor surgery under local anesthesia, patients experience 10% to 30% anxiety, with symptoms of tension, restlessness and worry. For major operations requiring general anesthesia, patients experience up to 20 to 50 percent anxiety, with symptoms of anxiety, excessive anxiety and sleep disorders. The aim is to determine the relationship between anxiety levels and comfort levels with the sleep quality of preoperative patients at Cilacap Regional Hospital. This research method is an analytical observational study with a cross sectional approach. The population of pre-operative patients at Cilacap Regional Hospital, sampling using Probability Sampling, was obtained as many as 60 respondents. The results of sleep quality and anxiety levels in patients have a p value of 0.044 which is below 0.05 which shows that the two variables have a significant relationship, while sleep quality and comfort level in patients have a p value of 0.015 which is below 0.05 which shows that the two variables have a significant relationship. There is a significant relationship between sleep quality, anxiety level and comfort level.